2021
DOI: 10.1038/s41467-021-27248-x
|View full text |Cite|
|
Sign up to set email alerts
|

Stroke subtype-dependent synapse elimination by reactive gliosis in mice

Abstract: The pathological role of reactive gliosis in CNS repair remains controversial. In this study, using murine ischemic and hemorrhagic stroke models, we demonstrated that microglia/macrophages and astrocytes are differentially involved in engulfing synapses in the reactive gliosis region. By specifically deleting MEGF10 and MERTK phagocytic receptors, we determined that inhibiting phagocytosis of microglia/macrophages or astrocytes in ischemic stroke improved neurobehavioral outcomes and attenuated brain damage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(112 citation statements)
references
References 69 publications
4
96
0
Order By: Relevance
“…Blocking the phagocytic receptors MerTK and the vitronectin receptors (integrins α v β 3 or α v β 5 ) can also prevent the phagocytosis of stressed neurons in stroke models [23,43]. Recently it was shown that the knockout of the phagocytic receptor MerTK, specifically in microglia and macrophages, reduced synaptic loss, brain atrophy and neurological deficits in mouse models of both ischemic and hemorrhagic stroke, whereas the knockout of the phagocytic receptor MEGF10, specifically in astrocytes, reduced synaptic loss and brain atrophy only in the ischemic model of stroke [65]. The latter finding suggests that phagocytosis by both microglia and astrocytes can be detrimental in ischemic stroke.…”
Section: Strokementioning
confidence: 99%
“…Blocking the phagocytic receptors MerTK and the vitronectin receptors (integrins α v β 3 or α v β 5 ) can also prevent the phagocytosis of stressed neurons in stroke models [23,43]. Recently it was shown that the knockout of the phagocytic receptor MerTK, specifically in microglia and macrophages, reduced synaptic loss, brain atrophy and neurological deficits in mouse models of both ischemic and hemorrhagic stroke, whereas the knockout of the phagocytic receptor MEGF10, specifically in astrocytes, reduced synaptic loss and brain atrophy only in the ischemic model of stroke [65]. The latter finding suggests that phagocytosis by both microglia and astrocytes can be detrimental in ischemic stroke.…”
Section: Strokementioning
confidence: 99%
“…ICH treatment with tES for one week could not significantly decrease these cells, although tRNS exerted a better effect. Nevertheless, the positive or negative role of gliosis in CNS repair remains to be elucidated [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…These two periods coincide with the peak of cerebral edema ( Manley et al, 2000 ). Moreover, AQP4 loss in mice can reduce astrocytes swelling and brain edema and improve neurological recovery after ischemia stroke ( Shi X. et al, 2021 ).…”
Section: Pathological Role Of Reactive Astrocytesmentioning
confidence: 99%
“…Phagocytic astrocytes can engulf synaptic components marked by presynaptic and postsynaptic proteins. Inhibition of this pathway can reduce the phagocytosis of astrocytes, improve neurobehavioral outcomes and alleviate brain injury ( Schilling et al, 2005 ; Morizawa et al, 2017 ; Shi X. et al, 2021 ).…”
Section: Pathological Role Of Reactive Astrocytesmentioning
confidence: 99%